Hemodynamics alterations during orthotopic liver experimental transplantation in pigs - Torres,Orlando Jorge Martins (2008)
PURPOSE: To describe the hemodynamics alterations during orthotopic liver transplantation in pigs. METHODS: In the period from April 2004 to December 2005, forty-four female Landrace pigs, weighting between 32 and 38 Kg were undergone to orthotopic liver transplantation. The animals were divided into two groups, donor and recipient pairs, which received whole liver grafts. The surgical procedure was divided into four parts: harvested, back-table, hepatectomy of the recipient and implantation. We analyze heart rate, blood gas, mean systemic arterial pressure (MAP-mmHg), central venous pressure, pH, Na-, K+, Cl-, Ca+ and urinary output. RESULTS: The mean anhepatic time was 69 min, cold ischemia was 252.2 min and back-table was 56.6 min. Blood pressure and heart rate dropped significantly during anhepatic phase and after revascularization. Blood gas and electrolytes alterations were observed during anhepatic and reperfusion phases. Although alterations were noted during these phases, the hemodynamic status was recovered and stabilized in the end of the surgery. CONCLUSIONS: Simplified technique of liver transplant was achieved and description of hemodynamic alterations was possible in pigs.